A new name in Sagina, Sagina alexandrae (Caryophyllaceae) - Iamonico, Duilio (Phytotaxa, 2016)
As part of the ongoing studies on the taxonomy and nomenclature of genera belonging to Caryophyllaceae Juss., contributing to the new edition of the Flora of Italy (see e.g., Iamonico 2013, 2014, 2016, Iamonico & Domina 2014, Iamonico & Sánchez Del Pino 2016, Vallariello et al. 2016), I here present a short note concerning a European species of Sagina Linnaeus (1753: 128) which is currently known as Sagina subulata (Swartz 1789: 45‒46) Presl (1826: 158).